AUGMENTED REALITY TECHNOLOGIES (VIRTUAL REALITY, AUGMENTED REALITY) IN THE INTELLECTUAL AND CREATIVE DEVELOPMENT OF CHILDREN - Shermanova Feruza Djumaboevna (Journals Park Publishing, 2023)
This article discusses and analyzes the integration of augmented reality technologies (Virtual Reality, Augmented Reality) into the content of education aimed at developing children's skills in working with information.
Keywords: Virtual reality, artificial reality, media education, intellectual and creative abilities.